2021
DOI: 10.2147/cmar.s287575
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of MicroRNA-130a Inhibits Oral Squamous Cell Carcinoma Proliferation and Metastasis via the Hippo-YAP Pathway

Abstract: Introduction Oral squamous cell carcinoma (OSCC) means oral epithelial cell injury caused by multiple genetic mutations of the cells. Dysregulation of microRNAs (miRs) can disrupt the progression of OSCC. This study explored the mechanism of miR-130a in OSCC progression. Methods miR-130a expression in OSCC cell lines was analyzed. Functional assays were utilized to test the alterations of OSCC cell proliferation, apoptosis and epithelial–mesenchymal transition (EMT) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For example, Lin et al reported that miR-31 played a pivotal part during the progression of OSCC through establishing a complicated network with its regulated genes and the signaling cascades such as EGF-AKT signaling axis, Hippo pathway, and Wnt signaling (57). Data from the study by Peng et al revealed that downregulation of miR-130a could inhibit OSCC proliferation and metastasis by the Hippo-YAP pathway, which may provide potential target for OSCC therapy (58). Previous studies have also demonstrated that miR-133a plays tumor suppressive role in OSCC by inhibiting the Notch signaling pathway via binding to CTBP2 (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lin et al reported that miR-31 played a pivotal part during the progression of OSCC through establishing a complicated network with its regulated genes and the signaling cascades such as EGF-AKT signaling axis, Hippo pathway, and Wnt signaling (57). Data from the study by Peng et al revealed that downregulation of miR-130a could inhibit OSCC proliferation and metastasis by the Hippo-YAP pathway, which may provide potential target for OSCC therapy (58). Previous studies have also demonstrated that miR-133a plays tumor suppressive role in OSCC by inhibiting the Notch signaling pathway via binding to CTBP2 (59).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the study by Peng et al. revealed that downregulation of miR-130a could inhibit OSCC proliferation and metastasis by the Hippo-YAP pathway, which may provide potential target for OSCC therapy ( 58 ). Previous studies have also demonstrated that miR-133a plays tumor suppressive role in OSCC by inhibiting the Notch signaling pathway via binding to CTBP2 ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Without timely and effective treatment, it frequently leads to deformities and death. The 5-year survival rate of OSCC is 55%, with a recurrence rate of 38% [ 38 ]. SNHG17 has been found to be significantly overexpressed both in OSCC cell lines [ 39 ] and clinical samples of OSCC patients compared to controls, and its expression levels were positively correlated with adverse pathological indicators [ 40 ].…”
Section: The Role Of Snhg17 In Cancersmentioning
confidence: 99%